2018
DOI: 10.1016/j.energy.2018.07.068
|View full text |Cite
|
Sign up to set email alerts
|

Positive interactions between electric vehicles and renewable energy sources in CO2-reduced energy scenarios: The Italian case

Abstract: Electric vehicles are progressively emerging in the light-duty passenger market as a promising alternative to oil-dependent road transport in the attempt to reduce greenhouse gas and pollutant emissions. However, it is necessary to investigate how a significant penetration of electric vehicles in the private transport fleet would affect the strategic planning of large scale energy systems.This study evaluates the integration of electric vehicles in the Italian energy scenario and their synergy with electricity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(47 citation statements)
references
References 42 publications
(42 reference statements)
2
33
0
12
Order By: Relevance
“…In general, previous studies have discovered the general sense of purpose of RES integration and relating EV diffusion [8], quantified the reduction in CO2 emissions and RES curtailments [9], deduced optimal levels of EV and RES penetration [10] and designed mechansims for the incentivisation of those [11].…”
Section: Introductionmentioning
confidence: 99%
“…In general, previous studies have discovered the general sense of purpose of RES integration and relating EV diffusion [8], quantified the reduction in CO2 emissions and RES curtailments [9], deduced optimal levels of EV and RES penetration [10] and designed mechansims for the incentivisation of those [11].…”
Section: Introductionmentioning
confidence: 99%
“…A reference scenario has been modelled with reference to the Italian energy system at 2016 with help of EnergyPLAN software, a computer model for energy system analysis. Data have been derived from updated and reliable sources following the procedure used in previous works of the authors [31]. Input data relevant to the analysis have been summarised in Appendix A listing main input parameters described in the following.…”
Section: Base Case Scenario Modellingmentioning
confidence: 99%
“…For example, Varone and Ferrari analysed the German energy scenario and pointed out that an eightfold increase in RES capacity, together with the adoption of P2G technologies, could result in a 79% RES share of total electricity generation [34]. In the Italian case, Romanelli estimated that, if RES were to generate an annual electricity production equal to the annual amount of electricity demand, RES capacity was required to increase, above the 2013 level, by a factor of 7.5-8.5 [2], while the authors found that full electrification of private transport and a tenfold increase in iRES capacity only result in 20% emission reduction and 58% RES share of electricity generation if no other measure is implemented [31].…”
Section: Renewable Energy Penetrationmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional aspect, that will be considered in detail, is the electricity production and distribution pathway: although electric cars are not causing local emissions, the electricity production may have other de-localized environmental impacts, especially if produced by fossil fuels. Focused studies are needed to promote synergies between EVs and a proper electricity generation from local RES (Bellocchi, Gambini, Manno, Stilo, & Vellini, 2018).…”
Section: Main Energy Sources For Passenger Transportmentioning
confidence: 99%